ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN - Nufus, Khayatun (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
Managing good finance is one of the fundamentals in company management, and usually use accounting information systems. This study aims to analyze the effectiveness of the sales accounting system. The analytical method used in this study uses a descriptive qualitative approach. So that this research can run effectively, the analysis technique used is by means of elaboration of Data Flow Diagrams (DAD) and Internal Control Questionnaire (ICQ) techniques. The analysis shows that the sales accounting system has been carried out according to procedure, however there are a number of things that need to be improved including HR and marketing team transaction evidence